A conceptual approach to developing biodiversity informatics as a field of science in South Africa - Parker-Allie, Fatima; Gibbons, Mark J.; Harebottle, Douglas M. (Frontiers in Ecology and Evolution, 2023)
In South Africa, as in other parts of the world, Biodiversity Informatics (BDI) has been identified as a young field of science that lies at the nexus of several disciplines, including informatics, biology and mathematics/statistics. Being such a new and dynamic field, there are challenges in the recruitment, training and retention of personnel that can support inter alia the mobilisation, management, coordination, and utilisation of biodiversity information for key conservation and biodiversity outcomes. The lack of human capital also places at risk the implementation of (e.g.) the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) and hinders attainment of the Convention on Biological Diversity post-2020 framework targets. There is therefore a clear demand for broad efforts to build human capital in the field. Using our experiences in South Africa, we provide a framework for establishing BDI as a field of science in developing countries and look at the potential building blocks towards this broad objective, including the need and requirements for the establishment of a Centre for BDI. We explore this concept against a backdrop of the South African government’s 2019 White Paper on Science, Technology and Innovation, and the associated Decadal Plan, both developed under the auspices of the Department of Science and Innovation. We also reflect on efforts in the broader landscape to look at the establishment of BDI curricula.